MAXIPOL: A Balloon-borne Experiment for Measuring the Polarization Anisotropy of the Cosmic Microwave Background Radiation - Johnson, B; Abroe, M; Ade, P; Bock, J; Borrill, J; Collins, J; Ferreira, P; Hanany, S; Jaffe, A; Jones, T; Lee, A; Levinson, L; et al. (2003)
We discuss MAXIPOL, a bolometric balloon-borne experiment designed to measure the E-mode polarization anisotropy of the cosmic microwave background radiation (CMB) on angular scales of 10 arcmin to 2 degrees. MAXIPOL is the first CMB experiment to collect data with a polarimeter that utilizes a rotating half-wave plate and fixed wire-grid polarizer. We present the instrument design, elaborate on the polarimeter strategy and show the instrument performance during flight with some time domain data. Our primary data set was collected during a 26 hour turnaround flight that was launched from the National Scientific Ballooning Facility in Ft. Sumner, New Mexico in May 2003. During this flight five regions of the sky were mapped. Data analysis is in progress.